Organ Size Regulation in Plants: Insights from Compensation - Horiguchi, Gorou; Tsukaya, Hirokazu (Frontiers in Plant Science, 2011)
The regulation of organ size in higher organisms is a fundamental issue in developmental biology. In flowering plants, a phenomenon called “compensation” has been observed where a cell proliferation defect in developing leaf primordia triggers excessive cell expansion. As a result, final leaf size is not significantly reduced compared to that expected from the reduction in leaf cell numbers. Recent genetic studies have revealed several key features of the compensation phenomenon. Compensation is induced either cell autonomously or non-cell autonomously depending on the trigger that impairs cell proliferation; a certain type of compensation is induced only when cell proliferation is impaired beyond a threshold level. Excessive cell expansion is achieved by either an increased cell expansion rate or a prolonged period of cell expansion via genetic pathways that are also required for normal cell expansion. These results indicate that cell proliferation and cell expansion are coordinated through multiple pathways during leaf size determination. Further classification of compensation pathways and their characterization at the molecular level will provide a deeper understanding of organ size regulation.